2019
DOI: 10.1002/mnfr.201800715
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Cells Deconjugate Resveratrol Metabolites to Free Resveratrol: A Possible Role in Tissue Factor Modulation

Abstract: Scope The antithrombotic effects of resveratrol (RV) and its derivatives remain unknown. The objective is to evaluate the modulatory effects of RV, its glucoside form, piceid, and its biological metabolites (RV‐3‐O‐β‐d‐glucuronide, RV‐4’‐O‐d‐glucuronide, and RV‐3‐O‐sulfate) on tissue factor (TF). Moreover, the endothelial metabolism of RV is assessed. Methods and results Human aortic endothelial cells (HAECs) are incubated with trans‐piceid, trans‐RV, or their biological metabolites and stimulated with tumor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
(105 reference statements)
5
16
0
Order By: Relevance
“…In addition, RSV was stable in the absence of cells, which accounts for the lack of spontaneous degradation and the complete availability of RSV for the cells. This stability is also consistent with results obtained in human endothelial cells incubated with different forms of RSV [31].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, RSV was stable in the absence of cells, which accounts for the lack of spontaneous degradation and the complete availability of RSV for the cells. This stability is also consistent with results obtained in human endothelial cells incubated with different forms of RSV [31].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, sustained intake of 1 g of RSV as a food supplement resulted in a concentration of 50-640 μM RSV in human colonic tissues [27]. Moreover, sulfate metabolites of RSV contribute to the in vivo activity of these metabolites by regenerating free RSV in colorectal cell lines, supporting the hypothesis that RSV metabolites potentially serve as a reservoir for the parent compound [27,195]. These paradigm shifting studies have not only challenged the classical notion that low bioavailability of RSV is the reason for the lack of therapeutic effects in human clinical trials but have also provided a potential molecular basis for the unexpected effects of high-dose RSV in human clinical trials such as adverse gastrointestinal effects [196,197].…”
Section: Rsv Attains High Micromolar Levels In Human Tissues and Plasmentioning
confidence: 77%
“…Previous authors have suggested that the low concentrations of the free forms observed in vivo cannot explain the biological activities associated with phenolic consumption in clinical and epidemiological studies [25]. Therefore, metabolites have been proposed as exhibiting relevant biological properties, either by having activity themselves or being deconjugated intracellularly giving rise to free active forms, as has been described for other dietary phenols [26,27]. In the present study we show an increase in TYR and HT phase II metabolite recovery following RW and beer treatments.…”
Section: Discussionmentioning
confidence: 99%